Validitas LKPD Berbasis Collaborative Argumentation Learning Model (CALM) untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik - Pramesti, Ardhia; Admoko, Setyo (IPF: Inovasi Pendidikan Fisika, 2024)
The purpose of this study was to evaluate the validity of worksheets based on the Collaborative Argumentation Learning Model (CALM) in order to improve students' science literacy level on alternative energy materials. An R&D approach combined with the ADDIE development model was the methodology used in this study. The three stages used in this research are: analysis, which involves identifying students' needs related to student worksheets on alternative energy materials; design, which involves organizing the worksheets created; and development, which involves collecting and validating the worksheets. The construction and content components of the LKPD can be used to evaluate its validation. One high school teacher and two knowledgeable lecturers became the three validators whose results were calculated as part of the data analysis technique. The advantages of the worksheets include being able to train science literacy indicators, using the argumentation-based CALM learning approach, and including real-world situations. The first recommendation from the validators was to pay close attention to the elements of scientific argumentation used as well as the signs of science literacy. The findings showed that the average validity score from the three validators was 96.21% for the content aspect and 97.22% for the construction aspect. This finding shows that the average value of the overall validity of the worksheet, with very valid criteria, is 96.72%. Thus, it can be said that the use of CALM-based worksheets to improve science literacy related to alternative energy content is appropriate for use during the educational process. This study shows that students benefit from using the argumentation component in physics learning, and this can be one way to help students become more savvy in science literacy.